Review of the backfire occurrences and control strategies for port hydrogen injection internal combustion engines. (1st January 2022) - Gao, Jianbing; Wang, Xiaochen; Song, Panpan; Tian, Guohong; Ma, Chaochen
Highlights: Backfire origins of hydrogen fuelled engines are comprehensively reviewed. Backfire control technologies of hydrogen engines are detailed discussed. Correlations between various backfire origins are analyzed. Different backfire control technologies are recommended adopting jointly. Abstract: Hydrogen fuel applications in internal combustion engines have attracted increasing attention due to zero carbon emission and excellent combustion characteristics in terms of thermal efficiency. Internal combustion engines fuelled with hydrogen are demonstrated to have higher brake thermal efficiency than other fossil fuel cases. However, abnormal combustion such as backfire in port hydrogen injection engines limits the improvement of internal combustion engine performance resulting from low ignition energy and high flame propagation velocity of hydrogen fuel. Volumetric efficiency drops significantly if backfire occurs; moreover, it brings about damages to the intake systems and fuel injection systems. Backfire is induced by high temperature residual exhaust gas, hot spots, and abnormal discharge of spark plugs; all the factors causing pre-ignition of hydrogen-air mixture promote the backfire occurrences. This paper reviews the factors tending to induce backfire, such as improper intake valve timing and fuel injection timing, and high fuel-air equivalence ratios; additionally, the corresponding backfire control strategies are analyzed with advantages and disadvantages being discussed. The factors leading to backfire are mainly caused by large amounts of residual exhaust gas, extremely slow combustion, and improper hydrogen distributions around intake valve seats. Backfire control strategies have specific application conditions to ensure their effectiveness, beyond which they will generate negative impacts on backfire control effectiveness. Power loss is nearly inevitable for naturally aspirated engines when backfire control strategies are adopted. Multiple control strategies are recommended to ease the engine performance drop caused by backfire control; meantime, multi-objective optimizations are suggested to achieve the optimal global performance.